Pengaruh Fear of Missing Out dan Citra Perusahaan Terhadap Keputusan Investasi Saham Oleh Generasi Z di Kota Medan: Penelitian - Muhammad Audri; Nicholas Marpaung (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the influence of Fear of Missing Out and corporate image on stock investment decisions. The focus of the study is on Generation Z in Medan City who have experience in investing in stocks at least once in the last three years. The research method used was quantitative with an associative approach. Data were collected through online and offline questionnaires distributed to 100 respondents selected using purposive sampling techniques. Data analysis was performed using multiple linear regression to determine the simultaneous and partial effects between independent and dependent variables. The results show that Fear of Missing Out and company image have a positive and significant influence, both partially and simultaneously, on Generation Z's stock investment decisions in Medan. These findings indicate that psychological factors and perceptions of companies are important considerations in investment decision-making.